2011
DOI: 10.1186/1475-2875-10-119
|View full text |Cite
|
Sign up to set email alerts
|

Selection of drug resistant mutants from random library of Plasmodium falciparum dihydrofolate reductase in Plasmodium berghei model

Abstract: BackgroundThe prevalence of drug resistance amongst the human malaria Plasmodium species has most commonly been associated with genomic mutation within the parasites. This phenomenon necessitates evolutionary predictive studies of possible resistance mutations, which may occur when a new drug is introduced. Therefore, identification of possible new Plasmodium falciparum dihydrofolate reductase (PfDHFR) mutants that confer resistance to antifolate drugs is essential in the process of antifolate anti-malarial dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Prior studies have shown that P. berghei and P. falciparum can share the same genetic basis of resistance to a number of antimalarial drugs, including pyrimethamine, atovaquone, and MFQ (67)(68)(69)(70)(71)(72). The same is not true for chloroquine however, which in the case of P. berghei and other rodent parasites has as-yet undefined mechanisms of resistance that do not appear to involve orthologs of pfcrt (64,73).…”
Section: Figmentioning
confidence: 75%
“…Prior studies have shown that P. berghei and P. falciparum can share the same genetic basis of resistance to a number of antimalarial drugs, including pyrimethamine, atovaquone, and MFQ (67)(68)(69)(70)(71)(72). The same is not true for chloroquine however, which in the case of P. berghei and other rodent parasites has as-yet undefined mechanisms of resistance that do not appear to involve orthologs of pfcrt (64,73).…”
Section: Figmentioning
confidence: 75%
“…Challenges such as reaching effective concentrations of the antibiotic in serum to select transgenic schistosomes in vivo might be encountered. However, at the present time, similar approaches are routinely applied to select transgenic protozoan parasites (56)(57)(58). Moreover, schistosomicidal drugs, including oxamniquine and praziquantel, have been employed to treat infected snails (59), paving the way for similar approaches with antibiotics, e.g., puromycin and neomycin.…”
Section: Discussionmentioning
confidence: 99%
“…To the first target category belong Pf enzymes in charge of generating nutrients required for malaria parasite growth. For instance, there are different biosynthesis pathways today used as targets for the discovery of antimalarial drugs such as the folate biosynthesis pathway [11][12][13]. The second target category includes pathways which mediate the uptake of nutrients into cells and the generation and maintenance of transmembrane electrochemical gradients, for instance, the plasmodial surface anion channel (PSAC) [14][15][16].…”
Section: Introductionmentioning
confidence: 99%